2023
DOI: 10.1029/2022jd037298
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a North America Ensemble Wildfire Air Quality Forecast: Initial Application to the 2020 Western United States “Gigafire”

P. Makkaroon,
D. Q. Tong,
Y. Li
et al.

Abstract: Wildfires emit vast amounts of aerosols and trace gases into the atmosphere, exerting myriad effects on air quality, climate, and human health. Ensemble forecasting has been proposed to reduce the large uncertainties in the wildfire air pollution forecast. This study presents the development of a multi‐model ensemble (MME) wildfire air pollution forecast over North America. The ensemble members include regional models (GMU‐CMAQ, NACC‐CMAQ, and HYSPLIT), global models (GEFS‐Aerosols, GEOS5, and NAAPS), and glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
(144 reference statements)
2
4
0
Order By: Relevance
“…Model 3 has the lowest false alarm rate, but also the lowest hit rate. Overall, the MMA ensemble works better than the individual models in extreme events air quality forecast, consistent with prior research (Li et al, 2020;Makkaroon et al, 2023).…”
Section: A Comparison Of Mma With Individual Modelssupporting
confidence: 89%
See 2 more Smart Citations
“…Model 3 has the lowest false alarm rate, but also the lowest hit rate. Overall, the MMA ensemble works better than the individual models in extreme events air quality forecast, consistent with prior research (Li et al, 2020;Makkaroon et al, 2023).…”
Section: A Comparison Of Mma With Individual Modelssupporting
confidence: 89%
“…Li et al (2020) used an ensemble forecast to predict surface PM2.5 during the 2018 California Camp Fire event using the National Oceanic and Atmospheric Administration (NOAA) Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) dispersion model with different emissions, plume heights, and model setups. Makkaroon et al (2023) successfully demonstrated a multi-model ensemble forecast system that effectively simulated the 2020 western US "Gigafire", with the ensemble mean outperforming individual models. These studies highlight the potential of ensemble forecasting to improve the predictability of wildfire air quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2020) used an ensemble forecast to predict surface PM 2.5 during the 2018 California Camp Fire event using the National Oceanic and Atmospheric Administration (NOAA) Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) dispersion model with different emissions, plume heights, and model setups. Makkaroon et al (2023) successfully demonstrated a multimodel ensemble forecast system that effectively simulated the 2020 western U.S. "Gigafire," with the ensemble mean outperforming individual models. These studies highlight the potential of ensemble forecasting to improve the predictability of wildfire air quality.…”
Section: Introductionmentioning
confidence: 99%
“…While multimodel ensemble often outperforms single-model forecasts, some challenges remain. The ensemble mean does not work best all the time (Xian et al 2019;Makkaroon et al 2023). For instance, insufficient diversity among models in the multimodel ensemble can limit the ability of the ensemble to capture the full uncertainties and variability tied to different inputs and assumptions.…”
Section: Introductionmentioning
confidence: 99%